Pengaruh kadar protein pakan yang berbeda dengan rasio E/P 8,5 kkal/g protein terhadap pertumbuhan ikan nila (Oreochromis niloticus) - Sefti Wulanningrum; Subandiyono Subandiyono; Pinandoyo Pinandoyo (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2019)
Feed utilization by tilapia (Oreochromis niloticus) was less optimal. Feed utilization efficiency (FUE) by tilapia could be improved by feed them with the suitable E/P ratio value of feed. This studi was aimed to examine the effect of various dietary protein with the E/P ratio of 8,5 kcal/g protein on the growth of nile tilapia. The experimental fish used was nile tilapia with the average body weight of 0,50±0,02 g/fish. The feed was given three times a day i.e. at 8.00 am, 12.00, and 4.00, pm by applied at satiation method. The experimental fish was maintained for 35 days with the density of 1 fish/l. The experiment used was completely randomized design with 4 treatments and 3 replicates. The treatments A, B, C, and D were trial feeds with protein content of 28, 30, 33, and 36% with DE content 240, 255, 280.5, and 306 kcal, respectively. The variables measured were total feed consumption (TFC), ratio efficiency protein (REP), specific growth rate (SGR), and survival rate (SR). The data showed that various dietary protein with equal E/P ratio resulted significantly effect (P<0,05) on FUE, REP, and SGR; but did not significantly effect (P>0,05) on TFC and SR. The TFC values of A, B, C, and D were 17,84±1,24, 18,70±0,28, 17,42±0,53, and 18,65±0,34 g; FUE values were 27,20±2,49, 38,19±3,84, 41,05±1,74, and 44,49±5,60%; REP values were 0,96±0,09, 1,28±0,13, 1,26±0,05, and 1,25±0,16%; and SGR values were 1,46±0,08, 1,94±0,28, 1,95±0,08, and 2,05±0,30%/day. The SR values of A, B, C and D were 100±0,00, 97,78±3,85, 97,78±3,85, and 95,33±4,04%, respectively. It was suggested that the increase of dietary energy and protein with a certain level of E/P ratio could improve the feed utilization efficiency and growth of tilapia